Examination of Smart Phone Addiction Levels of Students Studying At The Faculty of Sports Sciences - Söyler, Didem Yavuz; Bulut, Mesut (Erzurum Teknik Üniversitesi, 2025)
This study was conducted to investigate the smartphone addiction levels of students studying at the Faculty of Sports Sciences.The universe of the study consisted of 1743 students studying at the Faculty of Sports Sciences at Fırat University, while the sample consisted of 362 students studying at the Faculty of Sports Sciences, which was conducted using power analysis. The “Smartphone Addiction Scale (SATBS)” was used as the data collection tool in the study. The scale consisted of 33 items and has a score scale of 33 to 198. It is seen that the addiction level increases as the scores obtained from the scale increase. After entering the data into the licensed SPSS 24.0 package program, frequency, percentage and normality tests were performed in the statistical analysis of the obtained values, and then t-test was performed in paired groups and anova test was performed in multiple groups. Tukey Test was used to determine the differences between the groups.It was determined that the smartphone addiction levels of the students of the Faculty of Sports Sciences were below average, the age variable had no effect on addiction, and male individuals were more addicted in socially oriented relationships according to their gender. Again, according to the variable of the class they study, it was seen that students who are graduates are more addicted and individuals who change their phones every 2 years are more addicted. In the light of the findings obtained, suggestions can be made for future studies. It is recommended that the sample size be increased for the studies to be conducted, that the sample characteristics be paid attention to, and that the factor loadings of the scales be evaluated to increase the accuracy of the results to be obtained. It will also help in determining the factors affecting smartphone use and producing strategies in this direction.

Bu çalışma spor bilimleri fakültesinde öğrenim gören öğrencilerin akıllı telefon bağımlılık düzeylerinin araştırılması amacına yönelik yapılmıştır. Çalışmanın evrenini Fırat Üniversitesi Spor Bilimleri Fakültesi’nde öğrenim gören 1743 öğrenci oluştururken, örneklemi ise spor bilimleri fakültesinde öğrenim gören power analiziyle yapılmış 362 öğrenci oluşturmuştur. Araştırmada veri toplama aracı olarak, “Akıllı Telefon Bağımlılık Ölçeği (ATBÖ)” kullanılmıştır. Ölçek 33 maddeden oluşturulmuş ve 33 ile 198 puan skalasındadır. Ölçekten alınan puanlar arttıkça bağımlılık düzeyi de arttığı görülmektedir. Veriler lisanslı SPSS 24.0 paket programına girilerek elde edilen değerlerin istatistiki analizinde frekans, yüzde ve normallik testleri yapıldıktan sonra ikili gruplarda t testi çoklu gruplarda anova testi yapılmıştır. Gruplar arası farklılıkların belirlenmesinde ise Tukey Testinden yararlanılmıştır. Spor Bilimleri Fakültesi öğrencilerinin akıllı telefon bağımlılık düzeylerinin ortalamanın altında olduğu, yaş değişkeninin bağımlılığa bir etkisinin olmadığı ve cinsiyetlerine göre erkek bireylerin sosyal yönelimli ilişkilerde daha bağımlığı olduğu tespit edilmiştir. Yine okudukları sınıf değişkenine göre ise mezun durumunda olan öğrencilerin daha çok bağımlı olduğu ve telefon değiştirme düzeyleri 2 yılda bir olan bireylerin daha çok bağımlı oldukları görülmüştür. Elde edilen bulguların ışığında gelecekte yapılacak çalışmalara önerilerde bulunulabilir. Yapılacak çalışmalar için örneklem büyüklüğünün artırılması, örneklem özelliklerine dikkat edilmesi, elde edilecek sonuçların doğruluğunun artırılması için ölçeklerin faktör yüklerinin değerlendirilmesi önerilmektedir. Ayrıca akıllı telefon kullanımının etkileyen faktörlerin belirlenmesi ve bu yönde stratejiler üretilmesi konusunda yardımcı olacaktır.
Spor Bilimleri Fakültesinde Okuyan Öğrencilerin Akıllı Telefon Bağımlılık Düzeylerinin İncelenmesi
Keywords: Sports Science and Exercise (Other); Egzersiz ve Spor Bilimleri (Diğer)